Maternal Attachment to the Unborn Child A Developmetal Study - Adam, Bildfell Gale (My University, 1987)
Conclusions about the effects of pregnancy in women - how they feel about being pregnant and their attitudes to the unborn child - have been based almost exclusively upon observations of primigravidas. It is claimed that a satisfying and/or more stressful than later pregnancies. The research for this thesis suggests that some of these claims are mistaken.
This thesis examines the similarities and the differences between a group of primigravidas and a group of second pregnancy multigravidas on a range of maternal attitudes during pregnancy. The predictions were based on findings from a pilot study conducted at McMaster University Medical Centre. An interview was designed to elicit the women's thoughts and feelings about their expected infant and about themselves as mothers.
Primigravidas and multigravidas were found to be equally positive about the coming baby and equally anxious about their capacities as mothers. The primigravidas reported significantly more anxiety about the welfare of the expected infant and the multigravidas reported significantly more conflict and negative feeling. The common and unique features of a first and a second pregnancy are discussed. The findings suggest that new adaptations and family real realignments accompany the birth of each child.
A third sample of women was examined using the same measures. Comparisons were made between a group of multigravidas who had lost an infant by stillbirth or neonatal death and a group of multigravidas without a history of infant loss. Women who had previously lost an infant were found to be still mourning the death of the first infant and less invested in a relationship with the expected infant. The thesis discusses the effects of infant loss upon women and makes recommendations for the clinical management of bereaved mothers.
Keywords: Medical Sciences; Medical Sciences